2021
DOI: 10.1002/wer.1576
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potentially toxic element contamination in water of Şehriban Stream (Black Sea Region, Turkey) by using statistical and ecological indicators

Abstract: In the present study, the spatial–temporal variations of iron, lead, copper, cadmium, mercury, nickel, and zinc accumulations in the water of Şehriban Stream (northern Turkey) were investigated. Water Quality Index (WQI), Heavy Metal Evaluation Index (HEI), Pearson Correlation Index (PCI), and Factor Analysis (FA) were used in analyzing the water quality. Sampling was performed in 12 stations on monthly basis between February 2019 and January 2020 (a hydrological year). The data showed that the Şehriban Stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Moreover, previous studies showed that even the heavy metals that are necessary as nutrient element for organic development might be harmful to health when at high concentrations [35][36][37][38]. For this reason, many studies have examined the concentrations of heavy metals in soil [39,40], water [41][42][43], and air [44][45][46][47][48][49]. In recent years, the studies carried out on heavy metals were diversified more and many studies were carried out on heavy metal pollution caused by heavy metal sources such as traffic [50][51][52][53], industry [54], urban areas [55], and mining fields [56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies showed that even the heavy metals that are necessary as nutrient element for organic development might be harmful to health when at high concentrations [35][36][37][38]. For this reason, many studies have examined the concentrations of heavy metals in soil [39,40], water [41][42][43], and air [44][45][46][47][48][49]. In recent years, the studies carried out on heavy metals were diversified more and many studies were carried out on heavy metal pollution caused by heavy metal sources such as traffic [50][51][52][53], industry [54], urban areas [55], and mining fields [56].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature, precipitation, wind, and other environmental factors play a critical role in plant morphology, anatomy, and phenotypic features (Koç, 2021a;Ozel et al, 2021). Water may be one of the most crucial environmental stressors observed in the 21 st century worldwide (Mutlu and Kurnaz, 2018;Tokatli et al, 2021;Kutlu and Mutlu, 2021). Increased temperature increases the water usage by plants, resulting in a decline in water content in the soil called drought and water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very important to monitor the change in heavy metal concentrations in the water (Ucun et al, 2019;Ucun et al, 2020). There are also studies to determine the physicochemical properties of liquid for human health (Mutlu and Kurnaz, 2018;Demir et al, 2021;Tokatli et al, 2021). It is important to be given to rainwater harvesting in government policies, the amount of water to be disposed of before the first rain, underground water tanks, and rainwater storage tanks, maintenance, cleaning and importance of storage tanks, determining the purpose of use according to the quality of rainwater, microbiological and physicochemical effects of stored water on human health, the effect of fuel oil and fossil fuels on rainwater as a result of air pollution, the variation of rainwater quality between regions reasons, the effect of the material used in the rainwater collection area on the water quality will be the subject of the paper.…”
Section: Introductionmentioning
confidence: 99%